Early Neolithic Flint Assemblages from the Targowisko Settlement Region - Wąs, Marcin (Analecta Archaeologica Ressoviensia, 2022)
The article presents flint materials obtained from domestic facilities from the late phase of Linienbandkeramik from the Brzezie 40 and Targowisko 16 sites and the classic phase of the Malice culture from the 14–15 Targowisko site. These complexes contain relatively few monuments. Their advantage, however, is that they belong to chronologically compact groups. Since the relics of the discovered houses are spatially isolated from other settlement structures, it can be assumed that the set of flint artifacts belonging to them is relatively homogeneous. Thanks to this, they can contribute considerably to the discussion on the processes of cultural heterogenization and the origin of post-LBK cultures, including the Malice culture.